(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Siddiq AM, Kholiq N, Subchan W, Maulahila HI. 2023. Habitat suitability model for banteng (Bos javanicus) in Meru Betiri National Park, Indonesia. Biodiversitas 24: 1296-1302. In Indonesia, the population of banteng (Bos javanicus) has drastically dropped. The last line of defense against the continued existence of this species is provided by conservation areas like Meru Betiri National Park (MBNP). The purpose of this study was to evaluate the banteng’s habitat suitability in the MBNP region. The occurrence statistics from 2019 to 2020 collected by MBNP were sent to us. Three categories, i.e., direct encounter, footprint and dung encounter, and camera trap encounter are used to categorize the occurrence data. Eight environmental factors that we thought would affect the appropriateness of habitats and the distribution of banteng were incorporated into our modeling (land cover, altitude, slope, annual temperature range, annual precipitation amount, distance to the river and coastline, and distance to the nearest settlement). Utilizing MaxEnt v.3.4.4, the Habitat Suitability Model (HSM) was produced. In general, four environmental factors have a substantial impact, including; altitude, annual temperature range, distance from the nearest settlement, and the coastline distance to the settlement, distance to the coastline, altitude, and annual temperature range were the most significant variables according to permutation importance (PI) (35.1%, 22.2%, 11.8%, and 11.6%, respectively). According to our final HSM, the MBNP includes 33,891 Ha (65%) of inappropriate habitat and 17,985 Ha (35%) of habitat suitable for banteng. Finally, implementing habitat and population management for banteng in MBNP can use these results as guidance.